Effect of Disclosing Agents in Oral Hygiene - Frazão, Paulo; Sammarone, Mirella; Halk Villa, Silvia (Ciencia Odontológica, 2020)
Introduction: Dental caries and periodontal diseases are bacterial plaque-mediated oral health problems so disclosing agents have been recommended as auxiliaries in oral hygiene. Objective: The purpose of the present study was to assess the effect of disclosing agents in oral hygiene. Methods: A randomized double-blind crossover study was carried out using a 2% malachite green solution and criteria from Quigley & Hein (1962) index for effective comparison among 82 school children aged 11-13 years. First of all, adolescents were separated into thirteen groups. Seven groups were exposed to technique A (regular toothbrushing with disclosing agent and without dentifrice) and six groups to technique B (regular toothbrushing without disclosing agent or dentifrice). After three weeks, the subjects of technique A were exposed to technique B and vice-versa. Average plaque values were compared using Student’s t test. Results: The groups showed no difference between techniques, but significant differences were shown in both groups between the first and second steps. Conclusion: The results of this study show that disclosing agents play no crucial role in oral hygiene improvement. Explanatory hypothesis related to motivational effects engendered by the participation of the subject in the study are discussed.